Criminal Liability for Murder of Individuals with Schizophrenia - Jauhari, Syafah Diyana; Erna Dewi, Erna Dewi; Heni Siswanto, Heni Siswanto; Tontowi Jauhari, Tontowi Jauhari (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2025)
Criminal law aims to maintain social order by delineating prohibited and permissible conduct. Murder, as a material offense, prioritizes consequences—specifically, the unlawful deprivation of life—and necessitates proof of intent. When perpetrators exhibit mental disorders such as schizophrenia, a specialized assessment of their capacity for criminal responsibility becomes imperative. Article 44 of Indonesia’s Criminal Code (KUHP) explicitly exempts individuals unable to assume responsibility due to mental disorders from punishment. This study therefore examines the criminal liability of perpetrators who commit murder while diagnosed with schizophrenia, employing a qualitative methodology that integrates statutory and case-law approaches (analyzing Decisions 105/Pid.B/2023/PN.Gdt and 108/Pid.B/2021/PN.Stb). Key findings reveal stark disparities in court verdicts, attributable to inconsistent medical-legal evaluations of the perpetrators’ mental capacity. The research underscores that schizophrenia may serve as a valid excuse under Article 44 KUHP if evidence confirms the perpetrator’s inability to comprehend or control their actions. However, divergent judicial interpretations—based on psychiatric examinations (e.g., Visum et Repertum) and trial facts—highlight an urgent need for standardized assessment protocols. Crucially, the study demonstrates that criminal liability hinges not solely on the commission of unlawful acts (unlawfulness), but equally on the perpetrator’s ability to be responsible (toerekeningsvatbaarheid). To ensure justice and consistency, Indonesia must harmonize medical and juridical criteria for evaluating mental capacity in homicide cases involving schizophrenia.